2012
DOI: 10.1123/jsr.21.3.285
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Arthroscopic Partial Meniscectomy on Quadriceps Strength: A Systematic Review

Abstract: Context: Arthroscopic partial meniscectomy (APM) after meniscal tear has been widely accepted and associated with quick return to activity. Unfortunately, meniscectomy is associated with risk for knee osteoarthritis, which may be attributed to postsurgical quadriceps weakness. This has important implications, as the quadriceps play a prominent role in knee stabilization and energy attenuation in the lower extremity. Objective: To determine the magnitude of interlimb quadriceps strength deficits in people with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 34 publications
(83 reference statements)
1
30
0
Order By: Relevance
“…18 Additionally, partial meniscectomy has been associated with decreased quadriceps strength, which may alter lower extremity biomechanics and complicate the already decreased ability to attenuate energy at the knee. 57 We found that in patients with ACL rupture and meniscal damage, ACL-R and meniscectomy demonstrated greater prophylactic benefits in decreasing knee OA than in those with ACL-D who underwent meniscectomy.…”
Section: Discussionmentioning
confidence: 97%
“…18 Additionally, partial meniscectomy has been associated with decreased quadriceps strength, which may alter lower extremity biomechanics and complicate the already decreased ability to attenuate energy at the knee. 57 We found that in patients with ACL rupture and meniscal damage, ACL-R and meniscectomy demonstrated greater prophylactic benefits in decreasing knee OA than in those with ACL-D who underwent meniscectomy.…”
Section: Discussionmentioning
confidence: 97%
“…First, 5 studies failed to blind the assessor to the leg with the meniscal tear. Second, many studies (k = 6) did not account for body size when reporting strength, which we consider important as body size influences muscle strength . However, this was not considered problematic for cross‐sectional studies that compared strength to the contralateral leg, as there is no logical need to adjust for body size when comparing strength within participants.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the best efforts of clinicians and researchers to improve rehabilitative techniques, quadriceps weakness often persists long after rehabilitation concludes. [1][2][3] Given the importance of the quadriceps muscle to knee-joint health, it is critical that rehabilitation approaches that are capable of maximizing postoperative quadriceps function be identified.…”
mentioning
confidence: 99%